1984
DOI: 10.1111/j.1432-1033.1984.tb08391.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin and activators of protein kinase C modulate secretory responses of permeabilised human platelets induced by Ca2+

Abstract: Addition of thrombin enhances secretion of both [14C]serotonin and P-N-acetylglucosaminidase induced by Ca2+ in human platelets rendered permeable by exposure to intense electric fields. 2. Enhancement of P-N-acetylglucosaminidase secretion by thrombin results from an increase in the maximal extent of the response with no significant change in the median effective concentration EC,o for CaZ+. In contrast, thrombin shifts the dose/response curve for Ca2+-induced ['4C]serotonin secretion to the left and has litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…We have therefore performed studies in the presence of Mg CTP*-instead of Mg ATP'-since previous results have shown this nucleotide to be effective in supporting Ca'*-dependent secretion both in the presence and absence of thrombin [6]. Fig.3 demonstrates that addition of 20 PM ADP to such a system has no effect on the dose/response curve for [14C]5HT secretion induced by Ca'+.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have therefore performed studies in the presence of Mg CTP*-instead of Mg ATP'-since previous results have shown this nucleotide to be effective in supporting Ca'*-dependent secretion both in the presence and absence of thrombin [6]. Fig.3 demonstrates that addition of 20 PM ADP to such a system has no effect on the dose/response curve for [14C]5HT secretion induced by Ca'+.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of thrombin (a), adrenaline (b) and 5HT (c) on the Ca" dependence of [r4C]5HT release from permeabilised platelets in the presence and absence of GTP. Platelets suspended in a glycine-based medium (pH 6.6) [6], but containing 10 mM Na glutamate, 5 mM K glutamate, 2 mM Mg ATP*-and 1 mM BAPTA were rendered permeable as described previously [6] and then incubated for [6][7][8][9][10][11][12] In contrast, adrenaline (20/rM), when added in the presence or absence of 10 ,uM GTP, causes no significant shift in the dose/response curve for [14C]5HT secretion induced by Ca*+ (fig-lb). Similar results are obtained in the presence of 100 pM GTP or using adrenaline concentrations in the range 5-100,~M (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations